Incentive structure in telecom supply chain, production diversification, and rural resilience - Sharma, Priyanka (My University, 2025)
Rural economies worldwide face the problem of technological isolation and environmental instability, which creates both unprecedented challenges and opportunities for the rural communities seeking resilience in a rapidly changing landscape. This dissertation examines two different yet complementary aspects related to rural economic resilience through the open supply chain of telecommunication network infrastructure and agricultural systems. Rural development has become increasingly central to economic policy as decision-makers recognize its importance to overall economic growth. Although technology offers various solutions to rural resource constraints, telecommunications infrastructure remains disproportionately concentrated in population-dense regions. It creates fundamental disadvantage for rural communities, where businesses and farms need reliable and high-speed connectivity for modern operations. This gap between technological possibilities and rural realities occurs largely from how telecommunications networks are structured. Traditional vertically integrated mobile network supply chains have resulted in high costs, vendor lock-in, and standardized deployment strategies that prioritize dense urban centers while neglecting rural areas. Understanding the incentive structure of mobile telecom network stakeholders is therefore essential for developing viable solutions to bridge digital divide and enable rural regions to participate fully in the economy. The first essay provides a novel game-theoretic analysis of open radio access networks (ORAN) as an alternative telecommunications supply chain architecture. We assess strategic interactions between telecom supply chain stakeholders—mobile network operators (MNOs), network infrastructure suppliers (NIS), and original equipment manufacturers (OEMs)—across three procurement scenarios: (i) Traditional, (ii) Predatory as monolithic radio access networks (MRAN), and (iii) DirectOEM as ORAN. The second essay investigates how agricultural diversification strategies impact farm resilience in Kansas. Through panel data analysis spanning 2002-2022, the research documents that production diversification generally enhances farm income stability and improves financial resilience, especially during moderate drought conditions. It also suggests diminishing returns from diversification under extreme drought scenarios, highlighting diversification's limitations to be a sole risk management strategy. The findings from both studies converge on the importance of strategic adaptation in building rural economic resilience. The telecommunications analysis demonstrates how innovative network architectures and alternate supply chains can improve economic viability even in challenging rural markets, while the agricultural analysis quantifies how production diversification can buffer against unprecedented shocks. Together, these studies offer novel and empirically grounded recommendations for policymakers, network operators, and farmers seeking sustainable rural development pathways in response to technological disruption and environmental change. The research establishes that both technological innovation in telecommunications infrastructure and adaptive agricultural practices represent complementary pathways for strengthening regional economic systems in rural regions in the United States. By evaluating digital connectivity challenges and farm income vulnerabilities in various regions, this dissertation provides a framework to enhance rural regions' adaptive capabilities during shocks.
Keywords: Game theory; Telecommunication; ICT; Rural resilience; Simulation